2006
DOI: 10.1152/ajpcell.00082.2005
|View full text |Cite
|
Sign up to set email alerts
|

MAP kinase and calcium signaling mediate fluid flow-induced human mesenchymal stem cell proliferation

Abstract: Although the mechanisms by which osteoblasts and osteocytes respond to fluid flow are being elucidated, little is known about the mechanisms by which bone marrow-derived mesenchymal stem cells respond to such stimuli. Here we show that the intracellular signaling cascades activated in human mesenchymal stem cells by fluid flow are similar to those activated in osteoblastic cells. Oscillatory fluid flow inducing shear stresses of 5, 10, and 20 dyn/cm 2 triggered rapid, flow rate-dependent increases in intracell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
136
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 170 publications
(152 citation statements)
references
References 76 publications
(89 reference statements)
12
136
0
1
Order By: Relevance
“…This finding was consistent with the heterologously expressed TRPM7 in HEK293T cells [20]. [3], indicating that the IP 3 receptor (IP 3 R) may play an essential role. However, the exact IP 3 R subtype mediating Ca 21 release is still unknown.…”
Section: The Trpm7 Channel Independently Senses the Mechanical Stimulsupporting
confidence: 85%
See 2 more Smart Citations
“…This finding was consistent with the heterologously expressed TRPM7 in HEK293T cells [20]. [3], indicating that the IP 3 receptor (IP 3 R) may play an essential role. However, the exact IP 3 R subtype mediating Ca 21 release is still unknown.…”
Section: The Trpm7 Channel Independently Senses the Mechanical Stimulsupporting
confidence: 85%
“…This proposal is indirectly supported by another study showing that cilia mediated fluid flow mechanostimulaiton in human MSCs, and increased osteogenic gene expressions [27]. Fluid flow was also reported to induce an increase in intracellular calcium in human MSCs [3]. Furthermore, TRP channels located in the cilia can transduce the mechanical stimulation to calcium signals [28].…”
Section: Pressure Induces Trpm7-dependent Osteogenic Gene Expressionmentioning
confidence: 73%
See 1 more Smart Citation
“…One hour of oscillatory fluid flow exposure induces a significant increase in MSC proliferation via the activation of cell signaling cascades similar to those activated in more mature bone cells. 102 We demonstrated that fluid flow stimulates the activation of MAP kinase signaling as well as an increase in intracellular calcium concentration that leads to the activation of calcineurin, and pharmacological inhibition of these pathways abolished the effect of fluid flow on MSC proliferation. MSCs actively release ATP in response to a fluid flow stimulus, and this molecule leads to the activation of the signaling cascades necessary for fluid flow to induce proliferation.…”
Section: Fluid Flow In Tissue Engineeringmentioning
confidence: 77%
“…Skeletal flexion also promotes chondrocyte growth [Drescher et al, 2003]. Osteoblastic cellular responses include cell proliferation [Riddle et al, 2006], as well as diverse, generally anabolic, effects on differentiationand activity.…”
Section: Calcium-dependent Cellular Regulation In the Osteoblast And mentioning
confidence: 99%